(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the prosecutor’s powers and their limitations at the stage of initiating a criminal case, based on the provisions of the Criminal Procedure Code. The procedural involvement of the prosecutor in the pre-investigation verification process and the possibilities of influencing decisions on initiating or refusing to initiate criminal proceedings are examined based on legal norms.